The Ekman Streamfunction and the Eulerian and Residual Overturning Circulations of the Southern Ocean. Issue 17 (1st September 2021) - Stewart, K. D.; Hogg, A. McC.; England, M. H.; Waugh, D. W.; Kiss, A. E.
Abstract: The Ekman streamfunction is a wind‐derived metric that can be used to infer the Southern Ocean overturning circulations (SOOCs) in both latitude‐depth and latitude‐potential density spaces. The Ekman streamfunction integrates the Ekman pumping zonally and northwards from Antarctica, either to a given latitude or potential density. Here, we evaluate the relationship between the Ekman streamfunction and SOOCs in a global 0. 1 ° ocean‐sea‐ice model driven by interannual forcing (1958–2018). In certain regions of the Southern Ocean, strong correlations ( r > 0.9 ) exist between the Ekman streamfunction and the Eulerian and residual SOOCs on monthly and annual timescales. Regression analysis identifies regions where Ekman streamfunction variability coincides with > 4  Sv changes in the overturning; one such location is where the wind stress curl changes sign and the Ekman pumping is highly variable. Plain Language Summary: The global ocean overturning circulation is the planetary‐scale movement of waters in the vertical and north‐south directions. It is the principal mechanism by which the oceans absorb, sink, and redistribute heat and carbon from the atmosphere, thereby regulating Earth's climate. Despite its importance, it is impossible to observe directly, and must be inferred from sparse and infrequent proxy measurements. The main upward branches of the overturning circulation are located in the Southern Ocean, where strong westerly winds upwell waters from below. Thus, changes in these westerly winds will lead to changes in the overturning circulation, and, subsequently, Earth's climate. Here, we employ a diagnostic tool, called the Ekman streamfunction, to cast the change of the winds into a framework that is directly comparable with the overturning circulation. We use a state‐of‐the‐art global ocean‐sea‐ice model, in which the overturning circulation is measured directly, to examine the relationship between the Ekman streamfunction and the Southern Ocean overturning circulation. We find that throughout much of the Southern Ocean, the Ekman streamfunction is a robust indicator of the strength and variability of the overturning circulation, with exceptionally high correlation. Key Points: We examine the relationship between the Ekman streamfunction and the Eulerian and residual Southern Ocean overturning circulations (SOOCs) The Ekman streamfunction and SOOC exhibit striking similarities in both latitude and density spaces Where the wind stress curl changes sign, the Ekman streamfunction variability coincides with >4 Sv changes in the overturning circulation